Theoretical investigations on the structural stability, structural and physical properties, and bonding feature for RuX (X = Si, Ge, Sn) with B20 and B2 phases. (September 2020) - Zhang, Chuanzhao; Jin, Yuanyuan; Kong, Panlong; Li, Song; Chen, Shanjun; Zhang, Weibin; Cheng, Shubo; He, Kaihua; Dai, Wei
Abstract: A systematic first-principles study on the structural features and stabilities, bonding features and related physical properties of ruthenium compounds RuX (X = Si, Ge, Sn) with B20 and B2 configurations including the elastic, electronic and thermodynamic properties and Vickers hardness has been carried out by means of the pseudopotential plane-waves method. Based on the fourth-order Birch–Murnaghan equation of state, the phase transition pressures of RuSi and RuGe from B20- to B2-type were determined at 2.7 GPa and 9.0 GPa, respectively. Nevertheless, there is no structural phase transition in RuSn. The calculated formation enthalpies and elastic constants confirm that all six considered polymorphs are thermodynamically and mechanically stable. Additionally, the hardness value of B20-type RuX is higher than that of homologues B2-type RuX, which can be attributed to the stronger Ru-X covalent bond in B20 configuration than that in B2 structure. The analyses of DOS, ELF and Bader charges indicate that the chemical bonding in six crystals comprises a combination of covalent and ionic bonds with the sequence of the iconicity of RuSi > RuSn > RuGe for the same configuration RuX. The current theoretical findings will most likely promote further experimental and theoretical studies on Ru-based compounds.